LAPORAN KASUS : Infestasi Parasit Toxocara canis pada Anjing - Jayusman Arsiyanti Joesoef; Galuh Wiedani K.D Larasati (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
Dogs are often treated as family members but remain susceptible to various infectious diseases, including parasitic worm infections. Toxocariasis, caused by Toxocara canis, can compromise canine health and may lead to death. This article reports a case of T. canis infection in a dog. Diagnosis was performed through native and flotation fecal examinations, accompanied by blood profile analysis to assess changes associated with helminth infection. Fecal flotation revealed the presence of T. canis eggs, while blood analysis showed an develated eritrocyte count. Treatment was administered with an anthelmintic, and prevention is recommended through regular deworming and maintaining the cleanliness of the kennel and surrounding environment.